Two new species of Colubotelson Nicholls, 1944 in Tasmania's Lake Pedder: persistence of Phreatoicidae (Crustacea, Isopoda) in therein - Wilson, George D. F.; Osborn, A. W.; Forteath, G. N. R. (Zootaxa, 2012)
The Tasmanian lakes Pedder and Edgar were inundated in 1972 to create a reservoir to feed into a hydroelectric powerscheme, despite biologists highlighting the uniqueness of the fauna therein. This fauna included undescribed species ofphreatoicidean isopods, which were noted in several subsequent publications but not formally described. In 2010, the orig-inal beds of these two lakes were revisited and successfully sampled for these isopods as part of a program to assess theconservation status of the unique fauna of this large freshwater body. These two previously reported species of phreatoi-cidean are both new to science, distinct from each other and belong to the genus Colubotelson Nicholls, so we providedescriptions and illustrations of these species to assist their identification by other biologists. The two species are easilyidentified by the shape of the pleotelson and setation of the head, although they are separated by considerably more thantwo hundred specific differences. C. pedderensis sp. nov. was collected only from the now deeply submerged bed of theoriginal Lake Pedder, whereas C. edgarensis sp. nov. may be found more widely in the current extent of Lake Pedder,owing to its appearance in previously collected samples from the original Lake Pedder as well as in the now drowned areaof Lake Edgar. These results bring the known diversity of the family Phreatoicidae in Tasmania to 26 described species,including 16 in the genus Colubotelson. The persistence of phreatoicids in Lake Pedder, despite the extensive changes to its ecosystem, suggests that these two species are more resilient than was suspected.